Health Workers Attitude/Behavioural Influence on Women Access to Primary Health Care Services in Orumba North lga, Anambra State, Nigeria. - IGWE, IJEOMA; Ojua, Takim Asu; Atama, Chiemezie; 4UGWU, CHIDI; OBEKEZIE, D. S. (Archives of Business Research, 2014)
Lack of access to Primary Health Care (PHC) services has consistently posed serious health risks in Nigeria, especially in rural areas where health facilities are largely inadequate or absent in extreme cases. Cross-sectional survey research design was used to generate data for the study. Both quantitative and qualitative research approaches were used to investigate women who are responsible for caring their children to these PHC services. A total Six hundred women aged between 15-49 years formed the study sample and 600 questionnaires were administered by the researchers. Eight Focus Group Discussions (FGDs) with community members and in-depth interviews (IDI) with health workers were held. Results from multiple regression analysis with a <0.001 level of significance showed that the situation of PHCs in the study area was seriously poor and personnel problems which revolved around the attitude of health workers, and includes long waiting/appointment time given to patients or clients were the major challenges the people encountered in accessing PHC services in the LGA and these were supported by the qualitative data. The FGD data showed that mothers were often reluctant to visit the health facilities because of the shabby manner in which the health workers related and treated them. The study therefore recommends more Government presence in the rural areas in the form of provision of facility, medical consumables, employment of trained health workers and adequate sensitization and improved rural participation and capacity building workshops for workers on health issues. KEY WORDS: Access, Attitude, health workers, Primary Health Care Services.